Photoluminescence of Ag+ and Ag mn+ in co-doped Pr3+/Yb3+ fluorophosphate glasses: tuning visible emission and energy transfer to Pr3+/Yb3+ ions through excitation in different silver species - Castro, Tarcio [UNESP]; Jubera, Véronique; Fares, Hssen [UNESP]; Petit, Yannick; Fargues, Alexandre; Cardinal, Thierry; Nalin, Marcelo [UNESP]; Ribeiro, Sidney [UNESP] (Springer Nature, 2019)
Here, we report the luminescence properties of Yb3+/Pr3+ dual-doped fluorophosphate glasses containing silver clusters. Through the solubility of silver into the glass system as function of its initial concentration, charged species characterized as Ag+ and Agmn+ were formed and identified according to their absorption and emission spectral responses. By changing the transition metal concentration, multi-energy transfer mechanisms were observed between silver and Yb3+/Pr3+ co-doped glasses. The stabilization of silver species seems to be detrimental to the radiative processes of the rare earth ions under excitation at 444 nm (Pr3+3H4 → 3P0 absorption line). In other words, the main visible emissions of Pr3+ and the NIR emission of Yb3+ decrease with increment of Ag concentration. However, energy transfer occurs for large spectral range by the excitation of the silver species. In consequence, the visible and NIR emission could be activate in a broadband from ultraviolet to the blue part of the spectral region. These two observations highlight the competitive absorption processes and probabilities between the cationic elements and the interest to use the transition metal species as sensitizers to excite the rare earth elements.